Lesion durability found during mandated percutaneous catheter ablation after surgical cryo-ablation for treatment of non-paroxysmal atrial fibrillation - Bulava, Alan; Mokráček, Aleš; Němec, Petr; Wichterle, Dan; Osmančík, Pavel; Budera, Petr; Kačer, Petr; Vetešková, Linda; Skála, Tomáš; Šantavý, Petr; Chovančík, Jan; Branny, Piotr; et al. (Journal of cardiothoracic surgery, 2024)
OBJECTIVES: Current recommendations support surgical treatment of atrial fibrillation (AF) in patients indicated for cardiac surgery. These procedures are referred to as concomitant and may be carried out using radiofrequency energy or cryo-ablation. This study aimed to assess the electrophysiological findings in patients undergoing concomitant cryo-ablation. METHODS: Patients with non-paroxysmal AF undergoing coronary artery bypass grafting and/or valve repair/replacement were included in the trial if concomitant cryo-ablation was part of the treatment plan according to current guidelines. The patients reported in this study were assigned to undergo staged percutaneous radiofrequency catheter ablation (PRFCA), i.e., hybrid treatment, as a part of the SURHYB trial protocol. RESULTS: We analyzed 103 patients who underwent PRFCA 105 ± 35 days after surgery. Left and right pulmonary veins (PVs) were found isolated in 65 (63.1%) and 63 (61.2%) patients, respectively. The LA posterior wall isolation and mitral isthmus conduction block were found in 38 (36.9%) and 18 (20.0%) patients, respectively. Electrical reconnections (gaps) in the left PVs were more often localized superiorly than inferiorly (57.9% vs. 26.3%, P = 0.005) and anteriorly than posteriorly (65.8% vs. 31.6%, P = 0.003). Gaps in the right PVs were more equally distributed anteroposteriorly but dominated in superior segments (72.5% vs. 40.0%, P = 0.003). There was a higher number of gaps on the roof line compared to the inferior line (131 (67.2%) vs. 67 (42.2%), P < 0.001). Compared to epicardial cryo-ablation, endocardial was more effective in creating PVs and LA posterior wall isolation (P < 0.05). Cryo-ablation using nitrous oxide (N20) or argon (Ar) gas as cooling agents was similarly effective (P = NS). CONCLUSIONS: The effectiveness of surgical cryo-ablation in achieving transmural and durable lesions in the left atrium is surprisingly low. Gaps are located predominantly in the superior and anterior portions of the PVs and on the roof line. Endocardial cryo-ablation is more effective than epicardial ablation, irrespective of the cooling agent used.
Keywords: CryoMaze procedure; výsledek terapie; koronární bypass; Cryosurgery; Male; Staged hybrid ablation; Coronary Artery Bypass; Aged; Electrical conduction; mužské pohlaví; senioři; Catheter Ablation; Atrial Fibrillation; Pulmonary Veins; Treatment Outcome; lidé; ženské pohlaví; Humans; Gaps localization; Concomitant atrial fibrillation ablation; kryochirurgie; venae pulmonales; katetrizační ablace; Female; Electrophysiological study; lidé středního věku; fibrilace síní; Middle Aged